2020
DOI: 10.1111/ppl.13116
|View full text |Cite
|
Sign up to set email alerts
|

Decreased sink/source ratio enhances hexose transport in the fruits of greenhouse tomatoes: integration of gene expression and biochemical analyses

Abstract: To examine the physiological role of hexose transporters in determining the sink strength of individual fruits, the regulation of hexose transporters gene expression was studied when the sink/source ratio was artificially altered under the greenhouse condition; this was done in two cultivars of tomato, i.e. Grandella and Isabella. The sink/source ratio treatments included: saving one fruit per truss (1F), two fruits per truss (2F), three fruits per truss (3F) and no fruit pruning (control). The results showed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…This mainly occurs in the form of SAInv and A/NInv according to the optimal pH [70]. When plant cells respond to hexoses, these enzymes regulate the intracellular sucrose/hexose ratio [71]. In the present study, the genes (TaSAInv, TaA/NInv, and TaSPS) that catalyzed sucrose decomposition and synthesis were significantly up-regulated under the stress of Cd.…”
Section: Nahs Pretreatment Regulates the Related Gene Expression In W...supporting
confidence: 47%
“…This mainly occurs in the form of SAInv and A/NInv according to the optimal pH [70]. When plant cells respond to hexoses, these enzymes regulate the intracellular sucrose/hexose ratio [71]. In the present study, the genes (TaSAInv, TaA/NInv, and TaSPS) that catalyzed sucrose decomposition and synthesis were significantly up-regulated under the stress of Cd.…”
Section: Nahs Pretreatment Regulates the Related Gene Expression In W...supporting
confidence: 47%
“…These are the main exportable sugars in P. persica, and they were previously reported as the major soluble sugars in the leaves of this species (Moing et al, 1992). The increased content of exportable sugars together with the increase in the expression of sugar transporters related to phloem loading/unloading in response to thinning (Nuñez et al, 2019;Aslani et al, 2020) probably sustained the high metabolic rates and carbohydrate demand to sustain cell proliferation and endocarp lignification at S1 and S2 phases in fruit from thinned trees. We did not observe accumulation of these sugars in fruits, because once they arrived in the fruit, they were converted to glucose and fructose to sustain respiration and also directed to other biosynthetic pathways such as synthesis of cell wall components, amino acids, and precursors related to lignin synthesis.…”
Section: Discussionmentioning
confidence: 65%
“…In contrast, a decline in sugar content was observed in tomato [ 34 ], muskmelon [ 17 ] and mango [ 21 ] in response to carbohydrate limitation, and may be related to the time at which defoliation is applied during fruit growth. Among the enzymes involved in sucrose metabolism, invertase hydrolyzes sucrose to glucose and fructose, which contributes to the regulation of carbohydrates translocated into the sink tissues [ 35 ]. While acid invertase is mainly found in the vacuole and cell wall, neutral invertase is located in the cytoplasm [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Resulting glucose and fructose were then catabolized in the cytosol. A previous study also reported that acid invertase activity is enhanced for hexose unloading out of the vacuole, during the second stage of development in tomato fruits subjected to source/sink ratio change via pruning [ 35 ]. Glycolysis is the main pathway catabolizing hexoses in the cytosol.…”
Section: Discussionmentioning
confidence: 99%